APPLICATION OF ARIMA METHOD FOR RAINFALL FORECASTING IN ASAHAN REGION - Misshuari, Imas Wihdah; Kurniyaningrum, Endah; Saily, Randhi (Universitas Trisakti, 2023)
Rainfall forecasting plays a crucial role in disaster risk management and water resources management in urban areas such as Asahan, North Sumatera. This research explores the application of ARIMA (AutoRegressive Integrated Moving Average) model as a forecasting method to predict rainfall in Asahan, North Sumatera. Historical rainfall data from relevant meteorological stations were collected and used as the basis for developing the forecasting model. The ARIMA method involves identification, estimation, and diagnostic steps. A series of statistical analyses were conducted to determine the degree of autoregression (p), the time series that need to be integrated (d), and the degree of moving average displacement (q). The resulting ARIMA model was then tested on test data to evaluate forecasting accuracy. At this station, the accuracy is 50%, which means that rainfall forecasting at this station when using ARIMA(1,1,1) is quite accurate.